Body Composition Analysis in Young Pakistani Adults with Stable Ischemic Heart Disease versus Acute Coronary Syndrome - Nadeem, Muhammad; Azhar Ali Chaudhry; Bhatti, Qamar-Uz-Zaman; Ali, Rizwan; Haider , Iqbal; Zaman, Tahir (Pakistan Armed Forces Medical Journal, 2026)
Objective: To analyze the mean difference in total body composition on Bioelectrical Impedance Analyzer (fat percentage, lean body mass, visceral fat area, and segmental fat/muscle distribution) between young adults with SIHD and ACS. Study Design: Comparative cross-sectional study. Place and Duration of Study: Armed Forces Institute of Cardiology/National Institute of Heart Diseases, Rawalpindi Pakistan, from Aug to Nov 2025. Methodology: Two hundred patients (males aged 18–45 years and females aged 18–50 years) were enrolled using non-probability convenience sampling. Patients with acute illness, inflammatory conditions, or uncontrolled endocrine disorders affecting body composition were excluded. Participants were categorized into ACS-Group and SIHD-Group. Body composition was assessed using the InBody 270 analyzer in the upright position, with measurements performed in the morning after an overnight fast. Results: Among the 200 study participants, the ACS-Group (n=100) had a slightly higher median age [38.0 (32.0–44.0) years] than the SIHD-Group [34.0 (29.5–42.0) years, p-value =0.05]. However, ACS patients demonstrated a higher heart rate (92.08±14.61 vs. 78.96±12.46 bpm), greater skeletal muscle mass [38.08 (36.43–39.92) vs. 29.52 (28.04–31.12) kg], higher lean body mass [57.77 (56.21–59.66) vs. 49.29 (47.71–51.59) kg], and an elevated waist-to-hip ratio (0.93±0.09 vs. 0.902±0.09) compared with the SIHD-Group. Conclusion: Body composition parameters and lipid abnormalities contribute to early-onset coronary artery disease, with distinct patterns in ACS and SIHD. Incorporating body composition assessment into conventional risk evaluation may enhance risk stratification and support targeted prevention in high-risk young individuals.